Fur an imaginary portrait of Diane Arbus - Shainberg, Steven; Kidman, Nicole, 1967-; Downey, Robert, 1965-; Burrell, Ty, 1967-; Bosworth, Patricia; Picturehouse (Firm); River Road Entertainment (Firm) ([Los Angeles, Calif.] : New Line Home Entertainment, 2007)
Dramatizes the life of photographer Diane Arbus as she flees wealth, establishment, and her family to pursue her craft.
Inspired by the book "Diane Arbus: a biography" by Patricia Bosworth.
Originally released as a motion picture in 2006.
Special features: feature commentary with director Steven Shainberg, deleted scenes with commentary by director Steven Shainberg, Fur HBO first look, theatrical trailer.
Nicole Kidman, Robert Downey Jr., Ty Burrell, Harris Yulin, Jane Alexander.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Keywords: Arbus, Diane, -- 1923-1971 -- Drama; Bosworth, Patricia -- Film and video adaptations; Photographers -- New York (State) -- New York -- Biography -- Drama; Film adaptations; Feature films; Video recordings for the hearing impaired; Biographical films